Perbandingan Fungsi Produksi Padi Ciherang Sistem Jejer Legowo dengan Non Jejer Legowo di Kecamatan Sungai Tabukan Kabupaten Hulu Sungai Utara - Miranda Romaully; ahmad nor (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2013)
This study aimed to compare the function of Ciherang rice production, knowing the elasticity of production with jejer legowo systems and non jejer legowo in District Sungai Tabukan legowo Hulu Sungai Utara Regency, and provide recommendations for the research extension program implementation jejer legowo planting method. Research using primary data from 50 respondents farmers with jejer legowo systems and 50 respondent farmers with traditional systems. This research used Cobb-Douglass Production Function and predicted by OLS using SPSS version 20.  Production function predicted for jejer legowo planting system gives better results than the non jejer legowo system. Paired t-test value -5674 in 0.000 sig. showed that recommended planting method gave significantly different results than the traditional planting method. Production elasticity of each factor for production in non jejer legowo system with negative value showed farmers producing at irrational area (Stage III) is helping agriculture educators to show that jejer legowo planting method is better than the traditional way. However jejer legowo system was also not maximized its application. The use of capital inputs and fertilizers are recommended to add for the region I (irrational), while the others input need to be reduced to achieve a rational stage that allows farmers at optimum production level.